Teaching Climate Change in Primary Schools : an interdisciplinary process - Dolan, Anne M.; Dolan, Anne M. (Abingdon: Routledge, 2022)
"This important and timely book provides an overview of climate change and highlights the importance of including climate change education in primary schools. It emphasises the importance of cross-curricular pedagogical approaches with a focus on climate justice, providing in-depth assistance for teaching children aged 3 -13 years. Informed by up to date research, the book helps teachers to remain faithful to climate change science whilst not overwhelming children. Accompanied by online resources, this book includes practical and easy to follow ideas and lesson plans that will help teachers to include climate change education in their classrooms in a holistic, cross-curricular manner. Specific chapters address the following topics: inter-disciplinary approaches to climate change early childhood education pedagogies of hope the importance of reflective practice ideas for including climate change education in curricular areas such as literacy, geography, science, history, and the arts. Designed to promote climate change education in primary schools, this resource will help primary teachers, student teachers, geography specialists and all those interested in climate change education develop their own conceptual knowledge and that of the children in their class"--
Includes bibliographical references and index.
Keywords: Climatic changes -- Study and teaching (Primary); Environmental justice -- Study and teaching (Primary); Environmental education